Legal Review of Wills Based on Civil Law - Mahatulus, Rykson Thri; Tjempaka, Tjempaka (International Journal Labs, 2023)
Creating a will, also known as a testament, is a crucial legal process through which an individual shapes the destiny of their assets posthumously. Inheritances frequently give rise to a multitude of legal and social complications, necessitating the implementation of clear-cut regulations in accordance with prevailing legal norms. Wills serve as a vital instrument in averting conflicts among heirs, enabling the fulfillment of the deceased's final wishes. This process allows for a structured distribution of assets, thereby minimizing disputes and familial discord. However, the formulation of a will is subject to specific limitations and constraints, mandating adherence to relevant statutory provisions. These constraints may include requirements for witnesses, mental capacity assessments, and the legal age at which one can create a will. Discrepancies between legal statutes and societal customs regarding wills cast doubt on the continued suitability of existing regulations within the evolving legal landscape. Therefore, delving into the regulation of wills as stipulated in the Civil Code (Kitab Undang-Undang Hukum Perdata) is imperative to gain insight into the contemporary legal framework governing this matter in Indonesia. Thorough research into these legal provisions will shed light on their applicability and efficacy, aiding in the development of a more relevant and coherent legal framework for wills in Indonesian society. Such an updated framework would serve to better protect the rights and interests of individuals, ensuring that their final wishes are carried out smoothly and justly, while also reducing the potential for legal disputes and societal conflicts.